Attention as selection for action defended. - Wu, Wayne (Philosophy & Phenomenological Research, 2025)
Attention has become an important focal point of recent work in ethics and epistemology, yet philosophers continue to be noncommittal about what attention is. In this paper, I defend attention as selection for action in a weak form, namely that selection for action is sufficient for attention. I show that selection for action in this conception captures how we, the folk, experience it and how the cognitive scientist studies it. That is, selection for action pulls empirical and folk‐psychology together. Accordingly, philosophers who take seriously either source have reason to work with selection for action as their starting conception of attention. This conception provides a way to bridge empirical and philosophical concerns where attention is central. The theoretical advantages of selection for action have been obscured by the common opinion that it is easily refuted. I defend the position against many of the published objections and then deploy it to provide a foundation for the intuitive, but inchoate, idea of attention being gradable, something of which there can be more or less. An analysis of the gradability of attention is then applied to consider recent work on the harms due to a surplus of attention.